Analisis Pengaruh Disiplin Kerja, Pengalaman Kerja, dan Tingkat Upah terhadap Kinerja Karyawan - Putri, Rifa Nour Aini; Putri, Adnin Selviana (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Employee performance is one of the determining factors for a company's success in achieving organizational goals. This study aims to analyze the influence of work discipline, work experience, and wage levels on employee performance. This study uses a quantitative approach with a survey method by distributing questionnaires to respondents who are active employees. The results of the analysis show that work discipline has a significant effect on improving performance, work experience contributes to work effectiveness and efficiency, while wage levels have a positive correlation with employee motivation and loyalty. These findings indicate that companies need to pay attention to these three aspects in a balanced manner to optimize human resource productivity.